Management of von Willebrand disease type 3 during pregnancy - 2 cases reports. - Inocêncio, G. (2014)
BACKGROUND: von Willebrand disease type 3, is an extremely rare condition. It can be severe and potentially life-threatening, particularly in pregnant women during labor and subsequently during early puerperium. Due to its rarity, there is no optimal treatment/management during pregnancy. CASE: We describe two cases of pregnant women with von Willebrand disease type 3, and its successful surveillance and treatment with Haemate P FVIII (human plasma-derived von Willebrand Factor-ristocetin co-factor associated with human coagulation factor VIII), during pregnancy, partum and puerperium. CONCLUSIONS: Daily prophylaxis with Haemate P FVIII in women with von Willebrand disease type 3, starting 2 hours before caesarean section until the 7th day of puerperium, associated with close analytical and clinical surveillance seems to be a safe clinical option.